The impact of performance based costing technology in measuring the cost of consulting services : an applied study in the Office of Scientific and Consulting Services - University of Technology (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This research aims to apply the Performance Focused Activity Based Costing System in the offices of scientific and advisory services at the University of Technology for the purpose of measuring the cost of services provided by these offices in order to reduce costs. To test the hypothesis of the research, the research was applied in the consulting offices of the University of Technology through the financial statements for the year ending 12/31/2017 of the Scientific and Consulting Services Office of the University of Technology, because the data of these years were issued and audited by the Federal Office of Financial Supervision.A number of conclusions were reached, the most important of which are: reliance on traditional costing methods and techniques in measuring the cost of its services, which makes it unable to keep pace with developments in the business environment, as a result of its failure to properly determine the cost of its services, which is reflected negatively on profits. In addition, the use of costing technology based on activity based on performance would reduce costs, and help the management of these offices to continue to perform their work for a period of years.